"Is There a Doctor on Board?" The Plight of the In-Flight Orthopaedic Surgeon. Issue 8 (August 2019) - Scollan, Joseph P.; Lee, Song-Yi; Shah, Neil V.; Diebo, Bassel G.; Paulino, Carl B.; Naziri, Qais
Abstract : The most common in-flight medical emergencies are syncope, gastrointestinal distress, and cardiac conditions that include arrhythmias and cardiac arrests. Treatment algorithms for these emergencies are important to review and are included in this article. If confronted with a challenging in-flight medical emergency in which an orthopaedic surgeon believes that he or she is unable to offer sufficient help, consulting with ground-based physicians hired by the airlines is always an appropriate and readily available option. While providing care to the patient, the doctor is absolved from liability unless the care offered is grossly negligent and/or deliberately harmful. If the aircraft is registered in or is departing from countries within the European Union block or Australia, or if the patient is a citizen of one of those international bodies, the doctor is legally required to assist.